The Role Of Digital Marketing In Developing Rural Creative Economy - Faiza, Nur; Diantoro, Eman; Suheri, S; Hidayat, Syarif; Arianto, Bambang (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
This paper presents a study of the role of digital marketing in developing the rural creative economy in Indonesia. Micro, Small, and Medium Enterprises (MSMEs) in rural communities can benefit greatly from the simplicity and efficiency of digital marketing. However, the use of digital marketing is not yet fully optimized in Pandeglang Regency due to unequal internet infrastructure and lack of digital marketing skills. To address this issue, we conducted a qualitative study using in-depth interviews and observations with rural creative economy actors in the area. The data collected were analyzed using NVivo 12 Plus, a software program for qualitative data analysis. The results demonstrate that digital marketing has a positive impact on the development of the rural creative economy in Pandeglang Regency. This paper is essential to enhance digital marketing competencies and expertise among rural communities in the region to maximize the benefits of digital marketing. Our study contributes to the literature on rural development, creative economy, and digital marketing by providing insights into the challenges and opportunities of using digital marketing to develop rural areas.